Vitalitas Masyarakat Lokal Dalam Konservasi Budaya dan Lingkungan Menyongsong Pengembangan Bukit Ollon Sebagai Destinasi Wisata Unggulan Tana Toraja: The Vitality of Local Communities in Cultural and Environmental Conservation Leeps The Development Of Bukit Ollon as a Lead Tourist Destination in Tana Toraja - Limbu, Ineng Friska; Sonde, Rudolfo; Sanderan, Lady; Iftita, Nur; Suhasman, Suhasman (PERENNIAL, 2024)
Bukit Ollon is located in Ollon, Bonggakaradeng District, Tana Toraja Regency. Toraja Tourism is known for its beautiful panorama, where the charm of the natural beauty of Bukit Ollon combined with the uniqueness of the local culture is a superior value for Ollon, so if estimated, it can provide high income for Tana Toraja tourism. Seeing these advantages, research was conducted related to the cultural vitality of the Ollon community and the community's strategy to respond to the potential environmental degradation that will occur in Ollon and Bukit Ollon due to the increasing number of tourists who will come. The method applied is in-depth interviews and visual observations in the field while implementing strict health protocols. The results found that the current cultural vitality in Ollon is high. The level of degradation found in the Ollon environment is low. The Ollon community can survive with its unique culture, even though there are still cultural relics of ancestors such as Liang Saratu, which are still maintained and are still very rarely visited. With the opening of tourism doors in Ollon to become superior tourism, the whole community is ready to anticipate degradation.